Maternal and Perinatal Outcome of Twin Pregnancy in a Tertiary Hospital - Sultana, Masuda; Khatun, Sabera; Saha, Asim Kumar; Akhter, Parul; Shah, Abu Bakkar Siddique (Ibrahim Cardiac Medical Journal, 2013)
Ibrahim Cardiac Medical Journal 2011; 1(2): 35-39 DOI: http://dx.doi.org/10.3329/icmj.v1i2.13550